(3TQM GdebfY dehab GdOjf Hf bOGeI GdebOSis - (3Rjf GdOjf CHhGdHQcGJ Hf CHi YeQhYKeGf Hf CSYO GHf GdefLG GdJfhNi GdMfHdis; (3CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3cJGH GdHjY s
(3BNQgG (B:s
(3BNQ HGH GdhdGA s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B12 - (3U (B326 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1809s
Keywords: (3Gdabg GdMfHdjs